2008
DOI: 10.1590/s0034-72992008000300021
|View full text |Cite
|
Sign up to set email alerts
|

A bulimia nervosa como fator de risco para distúrbios da voz: artigo de revisão

Abstract: Bul imia nervosa (BN) is a type of feeding disorder that starts in adolescence and presents a variety of symptoms, recurrent vomiting in the oral cavity that may reach down to the larynx -similarly to gastro-esophageal reflux, causing laryngeal and voice disorder alterations. Aim: These studies aimed at surveying the literature and investigate the studies that considered BN a risk factor for voice disorders. Results: of the ninety three papers we found, twenty-three were used as a basis for this review, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
7

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 19 publications
2
0
0
7
Order By: Relevance
“…All the GRBASI scale parameters had higher severity values in the bulimia group, with statistically significance, matching reports from the literature which associates bulimia to vocal signs 26 . Results from the auditory-perception analysis revealed that most of the patients were considered mildly dysphonic by the examiners, and this was the predominant degree of change in all aspects evaluated.…”
Section: Discussionsupporting
confidence: 87%
“…All the GRBASI scale parameters had higher severity values in the bulimia group, with statistically significance, matching reports from the literature which associates bulimia to vocal signs 26 . Results from the auditory-perception analysis revealed that most of the patients were considered mildly dysphonic by the examiners, and this was the predominant degree of change in all aspects evaluated.…”
Section: Discussionsupporting
confidence: 87%
“…Nos anos 1970, esse transtorno alimentar era conhecido como Bulimarexia e, a partir dos anos 1980, o termo que passou a ser utilizado foi o de BN. Assim, etimologicamente, a palavra "bulimia" se origina do grego bous: boi e limos: fome 7,11 .…”
Section: Revisão Da Literatura 1 Bulimia Nervosaunclassified
“…Bulimia Nervosa (BN) é um distúrbio de comportamento caracterizado pela ingestão compulsiva de grande quantidade de alimentos, com pouco ou nenhum prazer, seguido de vômitos auto-induzidos com a finalidade de evitar o ganho de peso [1][2][3][4][5][6][7] .…”
Section: Introductionunclassified
“…A Tabela 4, representada por 12 artigos, revela claramente a relação entre a erosão e os dentes envolvidos, confirmando o maior acometimento do arco dentário superior (75%), bem como dos dentes anteriores (91,6%) da cavidade oral. (2,3,8,10,11,13,15,17,19,20,21,22,23,24,30) 15 / 48,3 Não se aplica Não se aplica…”
unclassified
“…Esse fato é justificado pelos conceitos contemporâneos de beleza, modismo, culto ao corpo e aparência social. Também os pacientes da raça branca, com elevado nível socioeconômico e cultural, inserem-se mais facilmente no grupo de risco, podendo, muitas vezes, não considerar a BN como um distúrbio de comportamento, mas sim um estilo de vida, o que dificulta o levantamento de dados epidemiológicos de ordem populacional no Brasil 10,11 . O início dos sintomas pode ocorrer nos últimos anos da adolescência ou até aos 40 anos, estando a média de início por volta dos 20 anos de idade.…”
unclassified